PENGARUH VARIASI KONSENTRASI CARBOPOL 934 SEBAGAI PENGENTAL TERHADAP SIFAT FISIK SEDIAAN SAMPO INFUSA DAUN PANDAN WANGI (Pandanus amaryllifolius Roxb.) - ASA FALAHI (AKADEMI FARMASI JEMBER, 2022)
The purpose of this study was to determine the effect of variation concentration carbopol 934 934 to the characteristics of physical shampoo from anti-dandruff infusion of pandan leaves (Pandanus amaryllifolius roxb). Pre-experiment one shot case study was used as a research design. Variation in carbopol 934 concentration were 1% (F1), 1.5% (F2), and 2% (F3) The result stowed that variation concentration of carbopol 934 affect organoleptic shape and smell, pH, and viscosity of shampoo. But didn’t affect color, homogenity, and foam height oh shampoo. The viscosity of the shampoo increases with the increase in the concentration of carbopol 934 used.